Effects of lime sulfur on Neoseiulus californicus and Phytoseiulus macropilis, two naturally occurring enemies of the two‐spotted spider mite Tetranychus urticae. Issue 3 (13th October 2019) - Vacacela Ajila, Henry E; Oliveira, Eugênio E; Lemos, Felipe; Haddi, Khalid; Colares, Felipe; Marques Gonçalves, Pedro H; Venzon, Madelaine; Pallini, Angelo
Abstract: BACKGROUND: The application of lime sulfur is a common practice used to control arthropod pests in organic production of fruits. However, the unintended effects of this insecticide preparation on non‐targeted organisms have not received the adequate attention. Here, we evaluated the lime sulfur toxicity on the phytophagous mites Tetranychus urticae Koch (Acari: Tetranychidae) and on two predatory mite species [i.e., Neoseiulus californicus (McGregor) and Phytoseiulus macropilis (Banks)] (Acari: Phytoseiidae) of natural occurrence in strawberry plants. We also assessed the repellency and potential effects on the oviposition rates and the egg viability of mites that were exposed to field‐used lime sulfur concentrations (i.e., 2%). RESULTS: The lime sulfur exhibited higher toxicity to the predators N. californicus (LC50 = 5.4 [4.5%–6.8%]) and P. macropilis (LC50 = 5.0 [4.0%–6.5%]) than to the phytophagous T. urticae (LC50 = 12.4 [9.0%–17.1%]). However, the exposure to field‐applied concentrations resulted in higher reductions on the oviposition rate of T. urticae (36%) than on the predatory mites ( N. californicus = 18%. P. macropilis = 19%). Interestingly, although the egg viability of P. macropilis was less affected (i.e., reduction of 50%) by such lime sulfur exposures, these mites were unable to avoid lime sulfur‐treated areas. Egg viability of N. californicus was only 18.6%. CONCLUSION: Lime sulfur at field‐applied concentrations harmed T. urticae fecundity and fertility and it showed selectivity against naturally occurring predatory mites, which reinforces its potential as a tool for integrated mite pest management. © 2019 Society of Chemical Industry Abstract : Unintended effects of lime sulfur on non‐targeted organisms have been overlooked. This study shows adverse effects of lime sulfur to naturally occurring predatory mites.